Solution of an elusive pigment crystal structure from a thin film: a combined X-ray diffraction and computational study. Issue 14 (17th March 2017) - Jones, Andrew O. F.; Röthel, Christian; Lassnig, Roman; Bedoya-Martínez, O. N.; Christian, Paul; Salzmann, Ingo; Kunert, Birgit; Winkler, Adolf; Resel, Roland
Abstract : The previously unknown crystal structure of epindolidione has been determined from a thin film by combining diffraction data with calculations. Abstract : Epindolidione, a hydrogen-bonded derivative of the organic semiconductor tetracene, is an organic pigment which has previously been used to produce stable OFETs with relatively high hole mobilities. Despite its use as an inkjet pigment and organic semiconductor, the crystal structure of epindolidione has proved elusive and is currently unknown. In this work, we report a crystal structure solution of epindolidione determined from vapor deposited thin films using a combined experimental and theoretical approach. The structure is found to be similar to one of the previously reported epindolidione derivatives and is most likely a surface-mediated polymorph, with a slightly different crystal packing compared to the bulk powder. The effect of substrate temperature on film morphology and structure is also investigated, where it is found that the crystallite orientation can be tuned by deposition at different substrate temperatures. The results also illustrate the possibilities for crystal structures to be solved from thin films.